1999
DOI: 10.1093/jnci/91.23.2001
|View full text |Cite
|
Sign up to set email alerts
|

Mercaptopurine Therapy Intolerance and Heterozygosity at the Thiopurine S-Methyltransferase Gene Locus

Abstract: We conclude that genetic polymorphism in TPMT is an important determinant of mercaptopurine toxicity, even among patients who are heterozygous for this trait.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
443
4
11

Year Published

2001
2001
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 669 publications
(481 citation statements)
references
References 34 publications
20
443
4
11
Order By: Relevance
“…Indeed, it has been shown that patients with TPMT deficiency tolerate high 6-TGN levels better than patients with normal TPMT activity. 35 Other side-effects due to AZA, including arthralgia, digestive intolerance and rash, did not recur under TG. Some of them have recently been attributed to the nitroimidazole metabolites released from AZA to give MP.…”
Section: Discussionmentioning
confidence: 92%
“…Indeed, it has been shown that patients with TPMT deficiency tolerate high 6-TGN levels better than patients with normal TPMT activity. 35 Other side-effects due to AZA, including arthralgia, digestive intolerance and rash, did not recur under TG. Some of them have recently been attributed to the nitroimidazole metabolites released from AZA to give MP.…”
Section: Discussionmentioning
confidence: 92%
“…In childhood ALL thiopurines constitute a major part of long-term continuing chemotherapy and it is important to identify treatment variables that could in¯uence the systemic exposure to active drug metabolites. TPMT activity has been related to the outcome and/or toxicity of therapy retrospectively [9,11,26]. For the TPMT de®cient child a knowledge of complete absence of TPMT activity can predict dose limiting severe myelotoxicity [13±15].…”
Section: Discussionmentioning
confidence: 99%
“…Rare individuals who are homozygous for loss of function variants are at high risk for bone marrow aplasia during therapy with standard doses, and this is stated in the package label. Ten percent of persons carry a single abnormal allele and are also at increased risk for bone marrow toxicity (18,19). Conversely, "standard" doses of mercaptopurine that are used in the 90% of patients with functional alleles mutations (see Glossary) may in fact be inadequate for achieving an optimal antileukemic effect (20).…”
Section: Coding-region Variantsmentioning
confidence: 99%